Aneurysm Size is the Strongest Risk Factor for Intracranial Aneurysm Growth in the Eastern Finnish Population. Issue 5 (15th May 2018) - Björkman, Joel; Frösen, Juhana; Tähtinen, Olli; Huttunen, Terhi; Huttunen, Jukka; Kurki, Mitja I; von und zu Fraunberg, Mikael; Koivisto, Timo; Manninen, Hannu; Jääskeläinen, Juha E; Lindgren, Antti E
Abstract: BACKGROUND: Saccular intracranial aneurysm (sIA) growth during follow-up is associated with high risk for subsequent rupture. Finnish patients have been suggested to have higher risk for subarachnoid hemorrhage, but follow-up studies of sIA growth in the Finnish population are scarce. OBJECTIVE: To identify the strongest risk factors for sIA growth in Eastern Finnish population by studying 205 patients with 350 unruptured sIAs with angiographic follow-up imaging. METHODS: In this population-based cohort study, we included unruptured sIA patients from the Kuopio University Hospital Intracranial Aneurysm Patient and Family database with at least 6 mo of angiographic follow-up after the diagnosis of sIAs. Angiograms were re-evaluated to detect aneurysms with growth of at least 1.0 mm. Cox regression analysis with patient- and aneurysm-related risk factors was used to calculate hazard ratios with 95% confidence intervals for growth. In addition, we tested the diagnostic value of previously introduced PHASES score for the prediction of sIA growth in Eastern Finnish population. RESULTS: Of the 350 unruptured aneurysms, 36 (10.3%) showed growth during median follow-up of 1.7 yr and total follow-up of 790 yr. In the multivariate Cox regression analysis, sIA size and location in the middle cerebral artery were significant risk factors for sIA growth. In receiver operator characteristic curves, both PHASES score and sIA size had relatively low areas under the curve. CONCLUSION: Our study indicates that aneurysm size is the strongest risk factor for aneurysm growth in Eastern Finnish population. Further studies are required to identify new risk factors for aneurysm growth.